Nutritional health : Strategies for disease prevention - Wilson, Ted; Jacobs, Jr., David R.; Temple, Norman J. (Nutrition and Health, 2012)
In its third much-expanded edition, the highly praised Nutritional Health: Strategies for Disease Prevention, Third Edition has been brought fully up to date to include all the new thinking and discoveries that have the greatest capacity to improve human health and nutritional advancement.  Drs. Temple, Wilson and Jacobs have organized this volume so that it provides an in-depth overview of the role of diet and dietary components in chronic disease prevention; the importance of public health actions, regulatory decisions and academic research in assuring the safety and efficacy of claims made on foods and dietary supplements.  About half the new edition has been revised and updated from the second edition while the other half consists of major revisions of previous chapters or new subjects. Like the two previous editions the book contains general reviews on various topics in nutrition, especially those of much current interest.  Up to date and comprehensive, Nutritional Health: Strategies for Disease Prevention, Third Edition offers physicians, dietitians, and nutritionists a practical, data-driven, integrated resource to help evaluate the critical role of nutrition.